Assessment of Quality of Life of Cancer Patients Due to Radiation Therapy – A Prospective Observational Study - Gudhoor, Manjula; Patil, Saikrishna; Sagar, Raghavendra D; Ganachari, Madiwalaya Shivakantayya (Indian Journal of Pharmacy Practice)
Background: Quality of Life (QOL) assessment is essential in cancer care, particularly for patients undergoing Radiotherapy (RT), which is administered to nearly 50% of all cancer patients. While RT improves survival, it often causes side effects impacting physical, emotional, social, and functional well-being. Existing literature shows varied QOL outcomes, underlining the need for ongoing evaluation and tailored supportive care. Objectives: To assess QOL changes in cancer patients receiving RT and explore influencing factors, with a focus on physical, emotional, social, and functional domains. Materials and Methods: A prospective observational study was conducted over six months (August 2024-January 2025) at a tertiary cancer hospital in Belagavi, India. A total of 93 adult cancer patients undergoing RT were evaluated using the Functional Assessment of Cancer Therapy-General (FACT-G) questionnaire. Clinical pharmacists monitored RT parameters (type, dose, duration) and provided supportive care. Statistical analyses included paired-sample t-tests and Pearson correlation.
Keywords: Quality of Life; Cancer; Radiotherapy; FACT-G; Emotional Well-being